A Comparative Study of Influence of Advertising through Online and Offline Media Channels on Consumers' Attitude by Selected Commercial Banks in Nairobi County, Kenya - Nancy, Kipchillat; Busolo, Hillary; Chepkilot, Ronald (International Review of Management and Marketing, 2019)
The of the aim of this study was to compare the influence of advertising through online and offline media channels on consumers' attitude as used by selected commercial banks in Nairobi County, Kenya. A cross-sectional study using a stratified sampling technique was used to sample the respondents from selected three commercial banks in Nairobi County, Kenya (Kenya Commercial Bank, Equity Bank, and Co-operative Bank). A sample size of 384 from three selected banks in Nairobi County was used. The data was then collected using a questionnaire, with questions comprising Likert scale type to measure consumers' attitude. The data was then analysed using SPSS software to determine descriptive and inferential statistics. The results revealed that TV (73.93) was ranked first followed by Google Ads (71.26%) by the consumers from the three selected bank. Offline media channel had highest overall score on consumer awareness (mean=3.552; CV=30.91%), liking (mean=3.491; CV=31.40%) and action (mean=3.454; CV=31.08%) compared to online media channels which had awareness (mean=3.02; CV=38.16%), liking (mean=2.913; CV=41.86%) and action (mean=2.881; CV=39.65%). Correlation analysis indicates that there was a strong and positive correlation between offline channels and consumers' attitude compared to online media channels. In addition, strong, positive and statistically significant relationship between use of TV and consumer awareness(r=0.799, p-value= 0.000), liking (r=0.898, p-value =.000) and consumer action tendency (r=0.718, p-value =.000). Regression analysis revealed that offline media channels significantly influence (F=3.994; p=0.0131) consumer attitudes compared to online media channels (F=2.551; p=0.0341) when accessing bank advertisement. Age had no significant moderating effect on offline media channels 78.5 % (R2=.559) and consumer attitudes whereas online media channel 55.9 % (R2=.559). In conclusion, this study has demonstrated that advertising through offline media channel by the selected bank significantly influence consumer attitudes and age plays no significant moderating effect on consumer attitude and media channels. Keywords: Advertising, Consumers' Attitude, Online Media, Offline Media JEL Classification: M3 https://doi.org/10.32479/irmm.8757